Identification of investment objects for the development of territorial natural recreational systems - Altaibayeva, Zh.K.; Bauer, M.Sh.; Alimkhanova, R.K. (BUKETOV BUSINESS REVIEW, 2019)
The authors gave the definition of «Territorial Natural-Recreational System» (hereinafter TNRS) and noted the importance of this definition for a capacious reflection of the content of the object in which economic, economic and geographical, ecological and sociological aspects of the recreational sphere were combined. In the article the author's opinion on the approach to the definition of investment objects in the project state program for the development of inbound and domestic tourism in the Republic of Kazakhstan for 2019–2015 was formulated, and an integrated approach to investing the development of TNRS was proposed to use. The possibilities of increasing the efficiency of attracted resources, which a comprehensive audit system opens up as a tool for identifying investment targets, are considered. The article notes that one of the main conditions for the development of TNRS is to bring it into compliance with the environmental standards of the environment, the technical standards of the infrastructure and international standards for the quality of recreational services. The authors presented a scheme that summarizes the objects of investment, determined by a comprehensive audit and presents an analysis of various points of view on environmental auditing, auditing compliance with technical standards of the infrastructure and international standards of recreational services. The proposed approach to the definition of investment objects on the basis of a comprehensive audit will ensure the effectiveness of attracted resources for the development of TNRS.